Mechanisms of change of a cognitive-existential group intervention for fear of cancer recurrence: mediation analyses of the FORT trial. Issue 3 (13th July 2022) - Lebel, Sophie; Maheu, Christine; Tomei, Christina; Mutsaers, Brittany; Bernstein, Lori J.; Courbasson, Christine; Ferguson, Sarah E.; Harris, Cheryl; Jolicoeur, Lynne; Lefebvre, Monique; Muraca, Linda; Ramanakumar, Agnihotram V.; et al.
Abstract: Background: Meta-analyses have demonstrated that brief interventions can address fear of cancer recurrence (FCR), but their mechanisms of action are largely unknown. Our goal was to identify the mediators of treatment efficacy of the Fear Of Recurrence Therapy (FORT) intervention using data from a multisite randomized controlled trial targeting FCR. That randomized controlled trial compared a 6-week cognitive-existential group intervention with an active control group. Methods: Participants (n = 135) were women diagnosed with stage I-III breast or gynecological cancer who were assessed at 4 time points (pretherapy, post-therapy, 3-month, and 6-month follow-up). The primary outcome, changes in FCR at 6 months, was measured with the Fear of Cancer Recurrence Inventory. We examined 6 mediators based on our theoretical model of FCR: perceived risk of recurrence, uncertainty in illness, intolerance of uncertainty, positive beliefs about worrying, reassurance-seeking, and cognitive avoidance. Changes in the possible mediator variables were simultaneously investigated to predict changes in FCR using Generalized Structural Equation Models with robust variance estimation. Results: FORT predicted FCR at 6 months in univariate analyses (β  = −8.93, P = .0001). In the model including the 6 possible mediators, changes in uncertainty in illness (β = −8.72, P < .0001) and cognitive avoidance (β = −8.36, P < .0001) mediated the relationship between treatment and changes in FCR. However, FORT still predicted changes in FCR at 6 months (β = −6.35, P = .02), suggesting partial mediation. Conclusions: We identified 2 mechanisms of action that can be incorporated in future interventions. However, other processes that underlie the efficacy of these interventions need to be uncovered.